What's in fake 'Xanax'?: A dosage survey of designer benzodiazepines in counterfeit pharmaceutical tablets. Issue 3 (1st July 2021) - Blakey, Karen; Thompson, Amanda; Matheson, Abbey; Griffiths, Andrew
Abstract: The identification of a range of different drugs within counterfeit benzodiazepine tablets has been widely reported; however, limited information is available on the dosage of these products. A rapid dosage survey of 46 counterfeit benzodiazepine tablets from 20 seizures was conducted over a 6‐month period between April and September 2020. Existing methods utilised for the determination of benzodiazepines in toxicology specimens were applied to assess the dosage of four benzodiazepines detected across five different counterfeit benzodiazepine presentations. The highest dosage variation was observed for etizolam with a range of 0.7–8.3 mg per tablet. This report demonstrates the variability in drug content and dosage that can occur between visually similar counterfeit tablets, even when co‐packaged within the same seizure, highlighting the potential public harm posed by these counterfeit medications. Abstract : Benzodiazepine dosages were assessed across five different presentations of seized counterfeit tablets. Drug content and dosage varied markedly between preparations, even in visually similar tablets co‐packaged within individual sealed containers, highlighting the potential risks associated with the use of counterfeit tablets. Etizolam was the most common benzodiazepine encountered in the tested counterfeit tablets, followed by alprazolam, flualprazolam, and flubromazolam.